The Syntax Analysis on Sentence Patterns Used in Louis Tomlinson Song Lyrics - Therendy, Therendy; Masrur, Masrur; Alamsyah, Alamsyah (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2024)
Syntax is the structure of sentences, the established rules of usage for arrangement of the words of sentence into their proper forms and relation. To get more understanding about syntax, the writer presents the syntax analysis on sentence patterns used in Louis Tomlinson song lyrics with album Walls by using the theory of sentence patterns by Quirk and Greenbaum. This research also used the theory of tree diagram by O’Grady, Dobrovolsky, and Katamba to help the writer in analysing sentence patterns. In this study the writer used qualitative method. The data of this research are words, phrases, and sentences related to the analysis of sentence pattern especially in Two of Us, Defenceless, and Kill My Mind song. From the result, through the sentences selected by the writer, the writer found that the most number of the sentence pattern in Louis Tomlinson’s song lyrics is sentence pattern number 3: S + Vt + dO which is used for 5 times.